Food utopias
1 online resource
Keywords: "In this book the authors link issues surrounding food and alternative food movements to the social science literature on utopias and intentional communities. The chapters address theoretical aspects of food utopias and also present case studies from a range of contexts and regions, including Argentina, Italy, New Zealand, Switzerland and USA. These focus on key issues in contemporary food studies including equity, locality, the sacred, citizenship, community and food sovereignty"--